Foraging behaviour of honeybees (Apis spp.) (Hymenoptera: Apidae) in hybrid seed production of Indian mustard (Brassica juncea) - MAITY, ANIRUDDHA; CHAKRABARTY, S K; YADAV, J B (The Indian Journal of Agricultural Sciences, 2014)
Pollination of entomophilous crops by honeybees is considered as one of the effective and inexpensive method for improving the crop yield and its quality. In most of the crops, effective pollination is prerequisite for fruitful fertilisation. Hence, we investigated the differential foraging activity of honeybees in relation to aspects of crop management including sowing time and parental row ratio in the hybrid seed production of the first Indian mustard hybrid NRCHB Apis spp. (half of which being Apis dorsata) was the dominant pollinators in our study. The pollinator abundance was maximum in the forenoon in male line (19.1) and in the afternoon in female line (13.9). Pollen collectors (8.7) outnumbered the nectar collectors (7.2) in male line and the reverse in female line. Pollinator abundance decreased in rows distantly positioned from the male parent row. Air temperature was positively correlated (r = 0.631) and relative humidity negatively correlated (r = –0.736) with honeybee foraging. Warmer weather conditions during flowering period showed higher number of honeybee visiting the hybrid seed production plots. This study would help the seed producers to standardise the planting geometry and date of sowing to promote maximum pollinator abundance at peak flowering period resulting in higher hybrid seed yield.